Gaya Bahasa dan Pemilihan Kata pada Podcast Rintik Sedu Episode "Kita Yang Terlupa": Language Style and Word Choice in the Rintik Sedu Podcast Episode“ Kita Yang Terlupa” - Rahmahwati, Nadhila Zahra; Hindun, Hindun; Yundiani, Sri; Putri, Zahra Amelia (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Language style or what we know as rhetoric is style. Language style is a distinctive way of expressing thoughts and feelings in written or oral form. Even though the choice of diction is correct, if the language style used is not interesting, then the diction is useless. This research aims to describe the rhetoric, diction and language style in the Rintik Sedu Podcast "We are Forgotten". The primary data source in this research is the Rintik Sedu podcast episode "Aku Yang Terlupa" which was then listened to and then recorded into a transcript. As for secondary data sources, this research uses books and journals related to rhetoric and those related to research conducted. The method in this research is a qualitative descriptive approach. The data collection technique in this research uses documentation techniques, notes, books and transcripts. The results of the first research show that the language styles used by the Rintik Sedu Podcast Host consist of simple language styles and intermediate language styles. Second, the diction used by the host of the Rintik Sedu Podcast consists of connotative diction and denotative diction.